Maternal postnatal mental health and later emotional-behavioural development of children: The mediating role of parenting behaviour - Cooklin, A R; Giallo, Rebecca; Wade, C; Nicholson, J; D'Esposito, Fabrizio (My University, 2014)
Background Maternal postnatal mental health difficulties have been associated with poor outcomes for children. One mechanism by which parent mental health can impact on children's outcomes is via its effects on parenting behaviour. Method The longitudinal relationships between maternal postnatal distress, parenting warmth, hostility and child well-being at age seven were examined for 2200 families participating in a population-based longitudinal study of Australian children. Results The relationship between postnatal distress and children's later emotional–behavioural development was mediated by parenting hostility, but not parenting warmth, even after accounting for concurrent maternal mental health. Postnatal distress was more strongly associated with lower parenting warmth for mothers without a past history of depression compared with mothers with a past history of depression. Conclusions These findings underscore the contribution of early maternal well-being to later parenting and child outcomes, highlighting the importance of mental health and parenting support in the early parenting years. Implications for policy and practice are discussed.
Child: Care, Health and Development
Keywords: Health -- Mental; Child Development; Families -- Mothers; Families -- Parents and Parenting; Childhood and child development; Families and relationships; Health and wellbeing; Child Development; Health; Families; Mental; Parents and Parenting; Mothers; Childhood and child development; Families and relationships; Health and wellbeing